Revisiting the new normal hypothesis. (September 2016) - Candelon, Bertrand; Carare, Alina; Miao, Keith
Highlights: Crises affect negatively output growth, supporting hence the "new normal" hypothesis. Banking crisis exhibits a negative effect only in the extended sample. Negative banking crisis effect is detected for high income OECD countries. Globalization does not always dampen the impact of the crises. Abstract: The paper estimates the impact of crises on output growth, augmenting Cerra and Saxena's (2008) analysis by extending the data until 2010, and by taking into account globalization and contagion effects. The paper finds that the decline in output growth rates following currency, banking and stock market crises are much larger in the sample ending in 2010, than in the one ending in 2001. The results are robust across different specifications and crisis databases. The paper finds that globalization, estimated using a factor augmented panel, has benefitted economic growth in the long run, but those gains have been diminishing in the new millennium. Moreover, globalization also amplifies the negative effects of crises, especially for upper middle and high income OECD countries, starting with the new millenium. As such, lower output growth is to be expected as the new norm, especially in these more advanced economies for a lot longer than what would have been expected in an usual cyclical recovery, confirming El-Erian and PIMCO's (2009) statement of a "new normal." Last, but not least, the estimation using a factor augmented panel leads to results consistent with thresholds effects of finance and growth, and of globalization on growth.